2018
DOI: 10.1111/opo.12450
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between homatropine and optical blur on choroidal thickness

Abstract: Homatropine appears to block the thinning effect of hyperopic defocus on choroidal thickness but did not enhance the thickening effect of myopic defocus. The changes in the choroid may relate to the different pathways in the eye's response to myopic and hyperopic blur or reflect an upper limit on the capacity of the choroid to thicken in the short-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 51 publications
(156 reference statements)
1
25
0
Order By: Relevance
“…administered 0.5 per cent atropine 22 hours prior to exposing subjects to −2.00 D hyperopic blur and found that prior atropine use negated the thinning effect of the hyperopic blur. Sander et al used two per cent homatropine in combination with ±3.00 D of blur and found that after 60 minutes, the homatropine had eliminated the thinning effect of minus blur, similar to the longer‐term findings of Chiang and Phillips . These findings suggest that a muscarinic pathway may be involved in the eye’s response to minus blur.…”
Section: Changes In the Choroid Associated With Environmental Factorsmentioning
confidence: 79%
“…administered 0.5 per cent atropine 22 hours prior to exposing subjects to −2.00 D hyperopic blur and found that prior atropine use negated the thinning effect of the hyperopic blur. Sander et al used two per cent homatropine in combination with ±3.00 D of blur and found that after 60 minutes, the homatropine had eliminated the thinning effect of minus blur, similar to the longer‐term findings of Chiang and Phillips . These findings suggest that a muscarinic pathway may be involved in the eye’s response to minus blur.…”
Section: Changes In the Choroid Associated With Environmental Factorsmentioning
confidence: 79%
“…Previous studies in human adults have measured short-term axial length changes in response to defocus after 30 minutes and 1 hour 20,21 . With myopic defocus, there were axial length reductions of 9 μm after 30 minutes and 13 μm after 60 minutes, and with hyperopic defocus there were axial length elongations of 5 to 9 μm after 30 minutes, and 8 to 11 μm after 60 minutes 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in human adults have measured short-term axial length changes in response to defocus after 30 minutes and 1 hour 20,21 . With myopic defocus, there were axial length reductions of 9 μm after 30 minutes and 13 μm after 60 minutes, and with hyperopic defocus there were axial length elongations of 5 to 9 μm after 30 minutes, and 8 to 11 μm after 60 minutes 20,21 . Our findings from the current study are consistent with these previous reports in young adults, with an average decrease of −7 µm with myopic defocus and an average increase of +9 µm with hyperopic defocus after 30 minutes which then peaked at ±10 µm of change after 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, changes in choroidal thickness after orthokeratology treatment remain equivocal, with various studies reporting either no significant changes during the first 9 months of lens wear,16 or an increase of approximately 20 μm in subjects wearing orthokeratology lenses for 3 weeks,17 6 months, and 1 year 18. However, some of these studies did not control for the influence of diurnal variation and performed measurements after cycloplegia, which is known to affect choroidal thickness and its response to defocus 1921. To date, only two studies have analyzed the correlation between changes in axial length and choroidal thickness in subjects treated with orthokeratology.…”
Section: Introductionmentioning
confidence: 99%